2019
DOI: 10.1111/jnc.14641
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the targeted metabolomic pathway in the hippocampus and comparative analysis with the prefrontal cortex of social defeat model mice

Abstract: The proportion of major depressive disorder (MDD) patients around the world has increased remarkably. Although many studies of MDD have been conducted based on classic hypotheses, like alteration of the hypothalamic–pituitary–adrenal axis or monoamine neurotransmitters, the mechanisms underlying MDD remain unclear. Aiming to further investigate the mechanisms of MDD, liquid chromatography–tandem mass spectrometry was employed to measure target metabolites in the hippocampus (HIPPO) of chronic social defeat str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 44 publications
(76 reference statements)
1
14
0
Order By: Relevance
“…Still, the pervasive neurotransmitter disorder in MDD makes it crucial to explore the underlying mechanism. As reported in our previous researches, altered monoaminergic neurotransmitters were confirmed in depression models of mouse [6], rat [7] and non-human primate [8], providing direct evidence for monoaminergic disturbance in MDD. Aside from changes in monoamine transmitters (serotonin, dopamine and norepinephrine), glutamate, the main excitatory neurotransmitter in central nervous system, has been reported to be involved in the pathogenesis of depression [9].…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…Still, the pervasive neurotransmitter disorder in MDD makes it crucial to explore the underlying mechanism. As reported in our previous researches, altered monoaminergic neurotransmitters were confirmed in depression models of mouse [6], rat [7] and non-human primate [8], providing direct evidence for monoaminergic disturbance in MDD. Aside from changes in monoamine transmitters (serotonin, dopamine and norepinephrine), glutamate, the main excitatory neurotransmitter in central nervous system, has been reported to be involved in the pathogenesis of depression [9].…”
Section: Introductionsupporting
confidence: 83%
“…The process of LC-MS/MS analysis was conducted as previously described [6]. In short, EC tissue samples were diluted in 400 µL methanol-water mixed solution (4/1, v/v, 0.1% formic acid) containing 75ng/ml L-Phe (2Cl)-OH as an internal standard.…”
Section: Lc-ms/msmentioning
confidence: 99%
“…Rabbit anti‐vMAT2 antiserum (Cat# ab70808, Abcam, ) was used to label vMAT2. Western blots of mouse brain homogenates recognize a band of approximately 57 kD via this anti‐vMAT2 antiserum (Xu et al, ); a detailed staining pattern in TH‐positive dopaminergic neurons has been previously described (Zhou et al, ). Rabbit anti‐CRH antiserum (Cat# T4037, Bachem, ) was also used in the present study and has been previously used in the mole and rat tissue for examining the presence of CRH neurons (Coen et al, ).…”
Section: Methodsmentioning
confidence: 97%
“…Rabbit anti‐AADC antiserum (Cat# ab3905, Abcam, ) was used to label AADC. Western blots of mouse brain homogenates using this anti‐AADC serum have been shown to label a single band at 53–54 kD (Xu et al, ), and its immunoreactivity patterns in the mouse midbrain and striatum have been previously described (Xenias, Ibanez‐Sandoval, Koos, & Tepper, ). Rabbit anti‐vMAT2 antiserum (Cat# ab70808, Abcam, ) was used to label vMAT2.…”
Section: Methodsmentioning
confidence: 98%
“…DA transmission in other brain areas is also involved in susceptibility or resilience to stress, although results are contradictory. Vulnerable mice were reported to display increased expression of DA D2 receptors in the amygdala[ 102 , 196 ] and increased levels of DA in the hippocampus and PFC[ 197 ]. However, another study found that hippocampal dopaminergic activity was inversely correlated with the level of social avoidance induced by SD and chronic treatment with hop bitter acids enhanced stress resilience[ 198 ].…”
Section: Advances Concerning the Neurobiological Substrates Of Resiliencementioning
confidence: 99%